Peran Kepala Sekolah dalam Pengembangan Bakat dan Minat Anak Berkebutuhan Khusus di SLB Negeri Muara Bulian - Zumroti Zumroti (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2023)
This study aims to describe the role of the principal in developing the talents and interests of students with special needs (SEN), to identify the programs provided for talent and interest development, and to examine their implementation at school. Efforts to enhance the abilities of SEN students face several challenges, particularly the limited availability of facilities and learning aids to support the development of each student's potential. This research employed a qualitative approach with data collected through observation, interviews, and documentation. The data were analyzed using the stages of data reduction, data presentation, and conclusion drawing. The findings reveal that the development of talents and interests at Sekolah Luar Biasa (Special School) Negeri Muara Bulian is primarily focused on practical skills designed to foster students’ abilities and prepare them for greater independence. Various skill-based programs have been implemented, including batik-making, gift arrangement, culinary arts, singing, and dancing. These programs aim to provide SEN students with not only academic enrichment but also practical competencies tailored to their potential, enabling them to be more empowered in daily life and future endeavors.